2003
DOI: 10.1152/jn.00547.2002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response Properties of Neurons in the Superior Paraolivary Nucleus of the Rat

Abstract: The superior paraolivary nucleus (SPON) is a prominent nucleus of the superior olivary complex. In rats, this nucleus is composed of a morphologically homogeneous population of GABAergic neurons that receive excitatory input from the contralateral cochlear nucleus and inhibitory input from the ipsilateral medial nucleus of the trapezoid body. SPON neurons provide a dense projection to the ipsilateral inferior colliculus and are thereby capable of exerting profound modulatory influence on collicular neurons. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
163
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(186 citation statements)
references
References 68 publications
21
163
2
Order By: Relevance
“…In contrast to the medial and lateral superior olives, neurons in the rat SPON are monaurally driven and show no evidence of binaural interactions (Kulesza, Jr. et al, 2003Kadner et al, 2006), suggesting that the MNTB/SPON circuit encodes a stimulus feature other than sound source location. Based on current knowledge of its response properties, we hypothesized that this brainstem circuit may be particularly well suited for encoding stimulus features associated with episodes of low or rapidly decreasing sound energy, such as tone offsets and the falling flanks and troughs in SAM stimuli.…”
Section: The Medial Nucleus Of the Trapezoid Body / Superior Paraolivmentioning
confidence: 93%
See 3 more Smart Citations
“…In contrast to the medial and lateral superior olives, neurons in the rat SPON are monaurally driven and show no evidence of binaural interactions (Kulesza, Jr. et al, 2003Kadner et al, 2006), suggesting that the MNTB/SPON circuit encodes a stimulus feature other than sound source location. Based on current knowledge of its response properties, we hypothesized that this brainstem circuit may be particularly well suited for encoding stimulus features associated with episodes of low or rapidly decreasing sound energy, such as tone offsets and the falling flanks and troughs in SAM stimuli.…”
Section: The Medial Nucleus Of the Trapezoid Body / Superior Paraolivmentioning
confidence: 93%
“…1A) (Kadner et al, 2006). The MNTB provides a strong glycinergic input to the nearby SPON (Helfert et al, 1989;Banks and Smith, 1992), whose neurons also display offset responses to pure tones; these however take the form of single or brief bursts of action potentials that occur after the stimulus offset (Fig 1B) (Kulesza, Jr. et al, 2003Kadner et al, 2006). Release from MNTB-derived glycinergic inhibition is critical to the formation of SPON offset responses, as demonstrated by reversible pharmacological blockade of glycine receptors in the SPON (Kulesza, Jr. et al, 2007).…”
Section: The Medial Nucleus Of the Trapezoid Body / Superior Paraolivmentioning
confidence: 99%
See 2 more Smart Citations
“…The superior paraolivary nucleus in rats provides an important exception because virtually all the cells in this nucleus project to the IC (Saldaña and Berrebi, 2000). Kulesza et al (2003) characterized the acoustically-driven responses of single units in the rat superior paraolivary nucleus. They concluded that the cells in this nucleus are important for encoding temporal features of sounds.…”
Section: Cortical Effects On Soc Cellsmentioning
confidence: 99%